2D and 3D Wear Analysis of 3D Printed and Prefabricated Artificial Teeth - Amna S. Al Saadi; Hatem M. El-Damanhoury; Nadia Khalifa (Elsevier, 2023)
ABSTRACT: Purpose: This study aimed to assess the 3-body wear of prefabricated and 3D-printed artificial denture teeth. Materials and methods: Four groups of artificial teeth were used; 3D-printed polymethylmethacrylate (PMMA) teeth (PR) and 3 prefabricated commercially available denture teeth: PMMA (Gnathostar, GN), PMMA (SR Orthotyp PE, SR), and Nanohybrid composite (SR Phonares NHC, PH). The 3-body wear test was performed using a steatite ceramic antagonist in a chewing simulator with 750,000 cycles, temperature 23 ± 2 ˚C, and force of 50 N. The abrasive medium was composed of ground millet seeds and white rice mixed with distilled water. The teeth were 3D-scanned before and after the wear test. The 3D images were assessed for teeth wear by measuring the volumetric (3D wear) and the vertical (2D wear) substance loss. The one-way analysis of variance followed by Tukey post hoc test was used to statistically obtain the data analysis. Results: Maximum 3D wear was observed in the PR (51.05 ± 4.53 mm³), followed by GN (20.22 ± 6.29 mm³) and SR (12.12 ± 6.29 mm³) artificial teeth. Minimum wear occurred in the PH teeth (6.24 ± 0.87 mm³). The analytical differences amongst the groups were statistically significant (P < .05) except between PH and SR teeth. For 2D wear measurement, the maximum was seen in the GN teeth (6.29 ± 1.64 mm), followed by PR (5.04 ± 0.83 mm) and then SR (4.53 ± 0.87 mm). The PH teeth (3.09 ± 0.68 mm) again showed minimum wear. Statistically, amongst the groups, the major observable differences (P < .05) were between PH and GN, PH and PR, and SR and GN. Conclusions: Composite resin teeth had a greater wear resistance than acrylic resin teeth and 3D-printed resin teeth, both of which were comparable. Due to the advancement of digital workflows, manufacturers should devote effort to enhancing 3D-printed teeth.